1977
DOI: 10.1002/1097-0142(197701)39:1<153::aid-cncr2820390126>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary blastoma. An ultrastructural study with a brief review of literature and a discussion of pathogenesis

Abstract: A pulmonary blastoma is reported in a 19-year-old black female. The light and electron microscopic characterics are described; they are found to be similar to those of the fetal lung prior to the fourth gestational month. Although the ultrastructural features do not favor any particular theory of histogenesis of this unique tumor, evidence for the commonly held theory that the tumor arises from pluipotential pulmonary blastema seems tenuous. A brief review of the literature disclosed 38 other similar cases. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

1979
1979
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…Several reports have shown that sputum analysis occasionally gives a false-positive test result as the mesenchymal tumor cells break through the bronchial epithelium and shed neoplastic cells. 13,15,16 Aspiration cytology and needle biopsy have been used to determine the nature of the tumor, 9 but the definitive diagnosis can only be made by histopathologic evaluation of a surgical biopsy. The aspiration cytology from our patient suggested neuroblastoma, but histopathologic diagnosis of the resected tumor confirmed a diagnosis of PB.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that sputum analysis occasionally gives a false-positive test result as the mesenchymal tumor cells break through the bronchial epithelium and shed neoplastic cells. 13,15,16 Aspiration cytology and needle biopsy have been used to determine the nature of the tumor, 9 but the definitive diagnosis can only be made by histopathologic evaluation of a surgical biopsy. The aspiration cytology from our patient suggested neuroblastoma, but histopathologic diagnosis of the resected tumor confirmed a diagnosis of PB.…”
Section: Discussionmentioning
confidence: 99%
“…Spencer (1961), following the former school and influenced by the peripheral development of the four tumours he had seen, felt it was logical to believe that they developed from lung mesoderm and thus should be named pulmonary blastoma. The supporters of the alternative theory of origin felt that, as they had demonstrated distinct epithelial and mesenchymal cell types on electron microscopy (McCann, Fu & Kay 1976, Fung et al 1977, the diagnosis of carcinosarcoma was more appropriate. Despite this opinion, they considered that the name pulmonary blastoma should be retained because of the distinctive clinicopathological features of tumours with and without embryonal differentiation.…”
Section: Embryology a N D C E L L O R I G I Nmentioning
confidence: 99%
“…1976). It is held that the cell lines found in this pulmonary tumour are quite separate and transformations from one to the other do not occur (McCann et al 1976, Fung et al 1977. This finding is disputed by others (Stackhouse, Harrison andEllis 1969, Davis et al 1972).…”
Section: Embryology a N D C E L L O R I G I Nmentioning
confidence: 99%
“…Spencer described four further cases in 1961 and renamed it "pulmonary blastoma." This type of neoplasm has recently been reviewed by Karcioglu and Someren (1974) and Fung et al (1977). About 40 cases have been reported at the time of writing.…”
Section: Pathologymentioning
confidence: 99%
“…Solid nests and cords or rosettes may also be seen (Marsden and Scholtz, 1976;Fung et al, 1977). Mitoses are often numerous.…”
Section: Pathologymentioning
confidence: 99%